Dietary Patterns Emphasizing the Consumption of Plant Foods in the Management of Type 2 Diabetes: A Narrative Review. (15th November 2019) - Salas-Salvadó, Jordi; Becerra-Tomás, Nerea; Papandreou, Christopher; Bulló, Mónica
ABSTRACT: The prevalence of type 2 diabetes (T2D) is increasing worldwide. This complex and multifactorial metabolic condition affects both the quality and expectancy of life in adults. Therefore, appropriate lifestyle strategies are needed in order to reduce the burden of T2D. Dietary patterns characterized by a high consumption of fruits, vegetables, whole grains, legumes, nuts, and seeds, and a minimal consumption of animal products, have been suggested as a dietary approach to prevent and control T2D and related micro- and macrovascular complications. This narrative review summarizes epidemiologic and clinical trial evidence on the role of the most widely studied dietary patterns that emphasize the consumption of plant foods [vegetarian, vegan, Mediterranean, and DASH (Dietary Approaches to Stop Hypertension) diets] in the management of T2D and its complications. Furthermore, their potential underlying mechanisms are discussed. Dietary patterns emphasizing the consumption of plant foods appear to confer beneficial effects on glycemic control in different diabetic populations. Several components of these dietary patterns might confer benefits on glycemia and counterbalance the detrimental effects of animal-based foods. The limited evidence on T2D-related complications makes it difficult to draw solid conclusions.